IMPLEMENTASI METODE PENGAJARAN SINERGIS DALAM MENINGKATKAN HASIL BELAJAR SISWA KELAS VIII PADA MATA PELAJARAN AL-QUR’AN HADIS DI MTS AR-ROSYIDIYAH BENGKALIS - Wahyuni, Sri; Chanifudin, Chanifudin (Jurnal Ilmiah Pendidikan dan Keislaman, 2024)
This research raised the theme of Implementation of Synergistic Teaching Methods in Improving Learning Outcomes of Class VIII Students in the Subjects of Al-Qur'an Hadith at MTs Ar-Rosyidiyah Bengkalis. This study aims to determine how the implementation of synergistic teaching methods in improving the learning outcomes of grade VIII students in the subject of Al-Qur'an Hadith at MTs Ar-Rosyidiyah Bengkalis. The reason for choosing the title is because by using synergistic teaching methods students can become more active and think critically. The formulation of the problem from this study is (1) How is the implementation of class VIII synergistic teaching methods on the subject of the Qur'an Hadith at MTs Ar-Rosyidiyah Bengkalis, (2) How much is the implementation of synergistic teaching methods in improving the learning outcomes of grade VIII students on the subject of Al-Qur'an Hadith at MTs Ar-Rosyidiyah Bengkalis. The underlying theory in this study is the Implementation of Synergistic Teaching Methods. The type of research used in this study is quasi-experiment obtained with test techniques and documentation. The results of this study show that there is an influence of synergistic teaching methods on student learning outcomes in class VIII Qur'anic Hadith subjects at MTs Ar-Rosyidiyah Bengkalis and is carried out well by proving that it conducts paired simple t tests. The results of the paired sample t test that have been carried out by researchers show that the results of the nig sig < t table are 0.000 < 0.05, it can be concluded that the synergistic teaching method affects student learning outcomes